Analysis of Phonological Errors in Arabic Reading Skills of Grade VII Students of MTs Darul A'mal Metro - Ajeng Retno Sari; M. Kholis Amrullah; Ahmad Habibi Syahid (Al-Kilmah: Jurnal Pendidikan Bahasa Arab dan Humaniora, 2025)
This study aims to analyze phonological errors in the reading skills of Arabic texts by grade VII students. Data sources were obtained from interviews with teachers and students, as well as recording the process of reading Arabic texts by students. The data was then analyzed through the identification and classification of phonological errors that occurred. This study identified various phonological pronunciation errors in students' Arabic reading skills, including the change of the phoneme ع to ء, such as in the pronounced بائع pronunciation, the change of the phoneme خ to ح such as أختي to أحتي, and the change of the phoneme ق to ك, e.g. the word سائق becomes سائك. This phonological error is caused by the limited knowledge of students in distinguishing phonemes that have adjacent articulations, as well as the lack of adequate reading practice, which results in inaccuracies in the pronunciation of letters and difficulties in understanding the meaning of reading.